Enhancing fire safety regulations for Malaysian student hostels; effective means of escape / Adnin Syaza Jaafar - Jaafar, Adnin Syaza (2024)
Higher education institutions (HEIs) play a vital role in developing a country’s human capital and workforce. The facilities provided by HEIs can create a conducive environment and promote positive teaching and learning experiences for students and staff members. One such facility is student hostels, which are crucial in providing an attractive learning environment, promoting unity, and fostering a vibrant student culture. There is a need to ensure that student hostels comply with building standards and have functionalities that guarantee the safety of the occupants. Due to the presence of large amounts of combustible materials in student hostels, proper evacuation measures must be in place for a safe evacuation to designated areas. In addition, student hostel buildings constructed based on outdated prescriptive building standards may not meet the requirements of current standards. Furthermore, there are significant differences in codes and regulations between countries. Therefore, this research aims to establish effective means of escape requirements for student hostels. This research has four objectives: first, to compare the means of escape requirements prescribed in the UBBL 1984 Amendment 2015 and the UBBL 1984 Amendment 2022 for student hostel; second, to distinguish the means of escape requirements outlined in the building standards of Malaysia, the United Kingdom, and the United States for student hostels; third, to assess the compliance of existing means of escape in student hostel based on the UBBL 1984 Amendment 2015; and fourth, to propose recommendations for enhancing the means of escape requirements in student hostels. A comprehensive literature review of the design requirements of means of escape is carried out throughout the research process. A qualitative method approach is used for data collection. The data collection is conducted in four phases. The data is collected using several methods, which include evaluation archival documents, walkthrough audits, and expert validation. The building standards used for comparison are UBBL 1984 (Malaysia), National Fire Protection Act 101 (the United States), National Fire Protection Act 1 (the United States), The Fire Safety (England) Regulations 2022: Approved Document B – Fire Safety (the United Kingdom), and British Standard. Two student hostels buildings in Malaysia are chosen as case studies and anonymously labelled due to privacy and confidentiality.